Implementation of Islamic Business Ethics for Inclusive Students in Qur'anic Perspective - Sulistianingrum, Sekar; Istanto, Istanto (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
The development of the world of work that is in great demand is the world of business/trade in percentage terms based on the main job business fields in 2021-2022, the highest percentage is in trade, business. In the development of business activities from the past until now, it is important to know that Islamic business ethics in the perspective of the Qur'an encourages entrepreneurs and business people to operate with integrity, honesty, and social responsibility while prioritizing blessings and mutual benefit based on the verses of the Qur'an. This observation or research aims to analyze, explain, and describe the implementation of Islamic business ethics from the Qur'anic perspective can provide a strong moral foundation for the inclusion of students in running their business. This helps them become responsible and ethical business leaders in society. This observation or research uses a descriptive qualitative approach method. This observation or research aims to analyze, explain, and describe the implementation of Islamic business ethics from the perspective of the Qur'an can provide a strong moral foundation for the inclusion of students in running their business. This research uses a descriptive qualitative approach method. The research technique is carried out in the form of data collection through observation, interview, and documentation methods. The results of the study can be described as follows based on the presentation of theoretical studies, research results, and analysis, which previously had been held observations made by the author at SMA Muhammadiyah 6 Surakarta. By understanding and applying Qur'anic principles in their business, inclusion students can contribute positively to the business world while living a life that is in accordance with their religious teachings.